Optimizing recovery: how PNF stretching and ice massage alleviate markers of DOMS? - Rachmah Laksmi Ambardini; BM. Wara Kushartanti (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2024)
Delayed onset muscle soreness (DOMS) is a common problem for both trained or untrained individuals that develop after eccentric or unaccustomed exercise. The large number of cases of DOMS and the varying results of research related to the prevention and treatment of DOMS, imply the importance of research in the effective DOMS prevention. The aim of this research was to investigate the post-exercise effects of combination Proprioceptive Neuromuscular Facilitation (PNF) stretching and ice massage on markers of exercise-induced muscle damage (DOMS). Thirty-nine subjects between the ages of 15 to 17 were randomly assigned to either the experimental or control groups. Subjects performed circuit training exercise-induced DOMS. The experimental group underwent 18 minutes of PNF stretching and 16 minutes of ice massage, which was given 2 hours after exercise. The control group did not receive any treatment. DOMS parameters (muscle soreness, creatine kinase/CK, aspartate aminotransferase/AST, neutrophil) and lower extremity functional scale (LEFS) were assessed at 0 and 24 hours after exercise-induced DOMS. The parametric and non-parametric different tests was used in data analysis. The experimental groups showed a reduction in DOMS symptoms in the form of less muscle soreness and AST, better LEFS compared to control groups (p<0.05), but not for creatine kinase and neutrophils (p>0.05) which is an indicator of tissue damage. In conclusion, the combination of postexercise PNF stretching and ice massage was effective in reducing the severity of DOMS, but it was not able to prevent DOMS.